Enhancing Presence, Immersion, and Interaction in Multisensory Experiences Through Touch and Haptic Feedback - Yang Gao; Charles Spence (Virtual Worlds)
In this narrative historical review, we take a closer look at the role of tactile/haptic stimulation in enhancing people’s immersion (and sense of presence) in a variety of entertainment experiences, including virtual reality (VR). An important distinction is highlighted between those situations in which digital tactile stimulation and/or haptic feedback are delivered to those (i.e., users/audience members) who passively experience the stimulation and those cases, including VR, where the user actively controls some aspects of the tactile stimulation/haptic feedback that they happen to be experiencing. A further distinction is drawn between visual and/or auditory VR, where some form of tactile/haptic stimulation is added, and what might be classed as genuinely haptic VR, where the active user/player experiences tactile/haptic stimulation that is effortlessly interpreted in terms of the objects and actions in the virtual world. We review the experimental evidence that has assessed the impact of adding a tactile/haptic element to entertainment experiences, including those in VR. Finally, we highlight some of the key challenges to the growth of haptic VR in the context of multisensory entertainment experiences: these include those of a technical, financial, psychological (namely, the fact that tactile/haptic stimulation often needs to be interpreted and can reduce the sense of immersion in many situations), psycho-physiological (such as sensory overload or fatigue), physiological (e.g., relating to the large surface area of the skin that can potentially be stimulated), and creative/artistic nature.